Comparison of effectiveness of the home exercise program and the home exercise program taught by physiotherapist in knee osteoarthritis - Yılmaz, Merve; Şahin, Mustafa; Algun, Zeliha Candan (IOS Press, 2019)
BACKGROUND: Home-based exercise therapy is effective in reducing pain and improving function in adults with osteoarthritis of the knee. OBJECTIVE: To investigate and compare the effectiveness of the home exercise program and the home exercise program taught by a physiotherapist in knee osteoarthritis. METHODS: The study was conducted with 80 patients with knee osteoarthritis. The patients were randomized into two groups. The first group was given the home exercise brochure by the orthopedist, while the second group did home exercises under the guidance of the physiotherapist. The goniometer for the range of motion (ROM) of the knee, Myometer for evaluation of the quadriceps and hamstring muscles strength, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and the Short Form Health Survey (SF-36) were used for evaluation. RESULTS: Statistically significant improvements were found in the post-treatment ROM, VAS, quadriceps and hamstring muscles strength, WOMAC and SF-36 values in both groups (p <0.05). When the change values were compared, the evaluation results of group II were better than group I statistically (p <0.05). CONCLUSIONS: This study proved that home exercises taught by a physiotherapist were more useful for patients with knee osteoarthritis. When the home exercise program is implemented, a new role is created for a physiotherapist.
WOS: 000460934600022
PubMed ID: 30248040
Keywords: Knee Osteoarthritis; Physiotherapy; Home Exercise; Exercise Education